Evaluasi Kepuasan Pengguna E-Learning pada Proses Pembelajaran Daring di Institut Manajemen Wiyata Indonesia - Eneng Fitri Handayani; Mariati Tirta Wiyata (ARIKA, 2020)
The research aims to obtain an overview of the (1) The quality of e-learning systems, (2) The quality of e-learning information, (3) The quality of e-learning services, and (4) e-Learning user satisfaction in the online learning process at the Institut Manajemen Wiyata Indonesia. This research uses the descriptive method of weighted average evaluative. Data collection is implemented by spreading the questionnaire. The results showed: (1) The quality of E-learning systems in the online learning process is categorized (well), (2) The quality of E-learning information on the online learning process is categorized (well), (3) The quality of E-learning services on the category of online learning is not good, (4) The satisfaction of E-learning users in the online learning process is categorized well.